A Near-Infrared Ratiometric Fluorescent Probe for Highly Selective Recognition and Bioimaging of Cysteine - Zhang, Xuan; Zhang, Li; Ma, Wei-Wei; Zhou, Yong; Lu, Zhen-Ni; Xu, Suying (Frontiers in Chemistry, 2019)
A benzothiazole-based near-infrared (NIR) ratiometric fluorescent probe (HBT-Cys) was developed for discrimination cysteine (Cys) from homocysteine (Hcy) and glutathione (GSH). The probe was designed by masking phenol group in the conjugated benzothiazole derivative with methacrylate group that could be selectively removed by Cys, and therefore an intramolecular charge transfer (ICT) fluorescence was switched on in the NIR region. In the absence of Cys, the probe exhibited a strong blue fluorescence emission at 431 nm, whereas a NIR fluorescence emission at 710 nm was significantly enhanced accompanied by a decrease of emission at 431 nm in the presence of Cys, allowing a ratiometric fluorescence detection of Cys. The fluorescence intensity ratio (I710 nm/I431 nm) showed a good linear relationship with Cys concentration of 1–40 μM with the detection limit of 0.5 μM. The sensing mechanism was explored based on MS experimental analysis and DFT theoretical calculation. Moreover, the fluorescent probe was successfully used for fluorescence bioimaging of Cys in living cells.